2015
DOI: 10.1161/circinterventions.114.001362
|View full text |Cite
|
Sign up to set email alerts
|

Stent Thrombosis and Dual Antiplatelet Therapy Interruption With Everolimus-Eluting Stents

Abstract: C urrent guidelines recommend dual antiplatelet therapy (DAPT) for at least 6 months (European Securities Committee)1 and 1 year (American College of Cardiology/ American Heart Association/Society for Cardiac Angiography and Interventions) 2 after drug-eluting stents (DES) to prevent stent thrombosis (ST), based on studies suggesting that firstgeneration DES are associated with increased rates of ST with premature DAPT discontinuation.3-6 Compared with bare-metal stents and first-generation DES, cobalt-chromiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 38 publications
3
28
1
Order By: Relevance
“…In the context of DAPT, it is worth noting that premature discontinuation of DAPT has been associated with an increased risk of stent thrombosis [68]. Two recent studies aimed to study the impact of sex on DAPT regimen after PCI.…”
Section: Dual Antiplatelet Therapymentioning
confidence: 99%
“…In the context of DAPT, it is worth noting that premature discontinuation of DAPT has been associated with an increased risk of stent thrombosis [68]. Two recent studies aimed to study the impact of sex on DAPT regimen after PCI.…”
Section: Dual Antiplatelet Therapymentioning
confidence: 99%
“…In this regard, some factors associated with increased risk of bleeding identified in the present report also have been associated with future ischemic events (e.g., advanced age, peripheral arterial disease, stenting of complex lesions)(15)(16)(17).Other variables, however, are uniquely associated with greater bleeding risk, such as baseline anemia and concomitant use of oral anticoagulation.Considering the individual patient's thrombotic and bleeding risk profile to personalize DAPT duration decisions should improve outcomes after DES implantation, although this decision-making process will remain challenging in some cases, and must incorporate patient preferences.The relationship between PDB and mortality is likely multifactorial (Central Illustration), including: 1) decrease in circulating blood volume and oxygencarrying capacity resulting in hypotension and propensity to ischemia and arrhythmias; 2) discontinuation of DAPT to manage bleeding, which compared to DAPT discontinuation for other reasons has been strongly associated with a higher risk of thrombotic events, especially when occurring within the first 30 days(18,19); 3) discontinuation of other life-extending medications to treat hypotension after bleeding, such as beta-blockers and angiotensinconverting enzyme inhibitors, which paradoxically often are not restarted after patient stabilization; and 4) administration of red blood cell transfusions and other blood products that have been associated with systemic vasoconstriction, activation of inflammatory pathways, apoptosis, increased platelet aggregation, and thrombosis (20). An interesting…”
mentioning
confidence: 99%
“…Furthermore, a network meta-analysis has indicated that the Xience stent has the lowest rate of stent thrombosis within 2 years of implantation among commercially available DES and also reduced stent thrombosis compared to BMS [24]. In addition, Généreux et al [25] have reported recently that DAPT discontinuation before 30 days after Xience stent implantation was strongly associated with stent thrombosis, whereas DAPT discontinuation beyond 90 days was not associated with stent thrombosis in a pooled analysis of 11,219 patients from 3 randomized trials and 4 registries with 2-year follow-up after stent implantation. Interestingly, and consistent with recently published analyses, our results indicate that CoCr EES reduced stent thrombosis in the early phase (EES: 1 vs. BMS: 4 episodes of early definite stent thrombosis), and this benefit persisted to 2 years (EES: 0 and BMS: 3 episodes of late definite stent thrombosis).…”
Section: Discussionmentioning
confidence: 99%